Visual evoked responses to reversal stimulation in the upper and lower half of the central part of the visual field in man - Kuba, M; Peregrin, J; Vít, F; Hanusová, I (Physiologia Bohemoslovaca, 1982)
Differences in visual evoked responses (VER) to three types of stimuli were studied in 70 volunteers, using checkerboard pattern reversal stimulation--a circular target in the central part of the visual field (VF) and stimuli composed of either the upper or the lower half of the circle. The responses to semicircular stimulation displayed great variability (latency shifts, reverse polarity, absence of a response), particularly to the upper half of the circle, where the amplitude of the responses was significantly smaller and their latency longer than in lower semicircle and whole circle stimulation.
Keywords: dospělí; lidé; Female; mužské pohlaví; Ocular Physiological Phenomena; Visual Fields; oči - fyziologické jevy; Evoked Potentials, Visual; Male; zrakové evokované potenciály; Adult; ženské pohlaví; zraková pole; Humans